2012
DOI: 10.1212/wnl.0b013e31823efcbb
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine treatment of mild cognitive impairment

Abstract: Objective: To preliminarily assess the safety and efficacy of transdermal nicotine therapy on cognitive performance and clinical status in subjects with mild cognitive impairment (MCI). Methods:Nonsmoking subjects with amnestic MCI were randomized to transdermal nicotine (15 mg per day or placebo) for 6 months. Primary outcome variables were attentional improvement assessed with Connors Continuous Performance Test (CPT), clinical improvement as measured by clinical global impression, and safety measures. Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(160 citation statements)
references
References 37 publications
8
143
3
1
Order By: Relevance
“…In view of the parallel reductions in ACh and nicotine binding sites in cerebral cortex, experiments were conducted to determine if nicotine could be a suitable treatment to restore cognitive function. Exposure to nicotine alleviated deficits in attention and informational processing associated with AD (Wesnes and Warburton, 1984;Sahakian et al, 1989;Newhouse et al, 2012). The positive effects of nicotine treatment observed in these studies were initially attributed to nicotine interacting with the high-affinity a4b2 nAChRs.…”
Section: A Alzheimer's Diseasementioning
confidence: 92%
See 1 more Smart Citation
“…In view of the parallel reductions in ACh and nicotine binding sites in cerebral cortex, experiments were conducted to determine if nicotine could be a suitable treatment to restore cognitive function. Exposure to nicotine alleviated deficits in attention and informational processing associated with AD (Wesnes and Warburton, 1984;Sahakian et al, 1989;Newhouse et al, 2012). The positive effects of nicotine treatment observed in these studies were initially attributed to nicotine interacting with the high-affinity a4b2 nAChRs.…”
Section: A Alzheimer's Diseasementioning
confidence: 92%
“…A genetic study suggested that the CHRNA7 might act as a modifier gene in patients with MCI in protection from conversion to AD (Barabash et al, 2009). A recent study demonstrated that in a 6-month study, transdermal nicotine improved measures of attention, memory, and mental processing in nonsmoking MCI patients, although not in the global impression clinical rating scale (Newhouse et al, 2012).…”
Section: A Alzheimer's Diseasementioning
confidence: 99%
“…A good number of NR products have been developed and licensed as effective treatments for tobacco dependence. However, nicotine isolated from tobacco has been tried as a treatment for many conditions and disorders and some positive effects have been observed in preliminary studies in the following conditions: ulcerative colitis (Sandborn, 1999), major depression (McClernon, Hiott, Westman, Rosse, & Levin, 2006), Tourettes's syndrome (Silver et al, 2001), neuroleptic-induced akathisia (Anfang & Pope, 1997), cognition in schizophrenia (Barr et al, 2008), attention deficit hyperactivity disorder (Gehricke Hong, Whalen, Steinhoff & Wigal, 2009), Parkinsons disease (Thiriez et al, 2011) and mild cognitive impairment (Newhouse et al, 2012). The best evidence is available for Parkinson's disease (Fagerström & Pomerleau, 1994;Thiriez et al, 2011) and ulcerative colitis (Green et al, 1997;Sandborn, 1999).…”
Section: Therapeutic Effects Of Nicotinementioning
confidence: 99%
“…These include intranasal insulin [37], melatonin [38], nicotine patches [39], Chinese plant extracts [40] and other antioxidants, various nutritional supplements (including vitamins and omega-3 fatty acids), ampakines , testosterone , metformin and levodopa. …”
Section: Pharmacological Treatment Of MCImentioning
confidence: 99%